2002
DOI: 10.1891/0730-0832.21.7.15
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships Between Mothers and Professionals in the NICU: Caregiving, Information Exchange, and Relationships

Abstract: Ratings of importance to the respondent and ratings of degree of implementation of items in the three areas were uniformly high. Mothers and nurses had significantly higher ratings than neonatologists in implementation of caregiving. In addition, mothers and nurses rated importance higher than implementation for the areas of information exchange and relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 9 publications
1
39
0
8
Order By: Relevance
“…At the same time, they had to learn how to fit in, work with staff and make sense of all the information they were presented with, most of which was in a new language (Bowie, 2004). McGrath (2001) describes these two-way working relationships formed between staff and parents, as 'guarded alliances', whilst Bruns and McCollum (2002) explored partnerships between professionals, i.e. neonatologists or nurses and nonprofessionals (mothers), in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they had to learn how to fit in, work with staff and make sense of all the information they were presented with, most of which was in a new language (Bowie, 2004). McGrath (2001) describes these two-way working relationships formed between staff and parents, as 'guarded alliances', whilst Bruns and McCollum (2002) explored partnerships between professionals, i.e. neonatologists or nurses and nonprofessionals (mothers), in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Bruns and McCollum (2002) revealed that positive parent-professional relationships could be developed when the parents felt that the health-care professionals recognized their caregiving skills and preferred ways of providing information and when the professionals were sensitive to their emotional needs. Therefore, it is important that health-care professionals recognize the family as a partner in caring for the child, in order to establish a favorable partnership with the family, and help individual families to gain more confidence and practical skills in providing for their child's care.…”
Section: Introductionmentioning
confidence: 99%
“…1 The hospitalization of a newborn in a NICU can be one of the most frightening and overwhelming experiences for a parent. 2,3 Families and providers have emphasized how stressful, difficult and emotional this time can be. [4][5][6] Family-centered care is becoming a standard of care in NICUs.…”
Section: Introductionmentioning
confidence: 99%